Serum vitamin D level and hypertensive crises - Hamid Reza Rashidinejad; Foad Amanolahi; Hossein Safizadeh; Mansour Moazenzadeh (Journal of Cardio-Thoracic Medicine, 2018)
Introduction :Vitamin D deficiency is associated with hypertension; however, there is no study on the relationship between vitamin D deficiency and hypertensive crises. This study aimed to determine the relationship between serum vitamin D levels and hypertensive crises. Materials and Methods: This descriptive-analytical, cross-sectional study was conducted on 120 individuals in Shafa Hospital in 2016 within the age range of 40-80 years, selected through simple random sampling technique. The research population was divided into two groups of hypertensive crises (n=60) with blood pressure over 180/120 mm/Hg and hypertensive patients without history of hypertension crises (n=60). For the purpose of the study, 5 ml peripheral venous blood samples were collected. The blood serum was isolated by a centrifugal device, and the serum vitamin D levels were analyzed by radioimmunoassay. Results: The meanlevels ofvitamin D in hypertensive and non- hypertensive crises groups were 29.73 and 30.23 ng/ml, respectively. There was no significant difference between the two groups in terms of vitamin D levels (P>0.05). However, no statistically significant difference was observed between the two groups considering gender (P>0.05). Serum vitamin D levels showed a direct correlationwith theduration of hypertension and age (P Conclusion:There is evidence on the relationship between serum vitamin D levels and cardiovascular diseases, including hypertension. Nonetheless, in the present study, no significant relationship was observed between serum vitamin D level and hypertensive crises.